(NiZMERENIE SME]ENIJ OPOLZNEJ (B/s - (NgRIGORENKO(B, (NaNATOLIJ gRIGORXEWI^s ((NmOSKWA (B:s (NnEDRA(B,s, 1988)
(NbIBLIOGR(B.: (NS (B. 143 (9 (NNAZW(B.)s
Keywords: (NoPOLZNI (B- (NiNVENERNO(B-(NGEOLOGI^ESKIE ISSLEDOWANIQs